The Study of the Structure of the Krasnodar Territory Contemporary Steppe Landscapes - KRIVOROTOV, Sergey B.; NAGALEVSKY, Eduard Yu.; VOLKOVA, Tatiana A.; GOLUBYATNIKOVA, Ekaterina V. (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
As a result of lichenological and lichenocenological studies in the steppe plant communities of the Taman Peninsula, 40 species of lichens from 19 genera and 11 families were identified. To determine lichens, traditional methods in lichenology were used. The taxonomic list of lichens is compiled taking into account the current nomenclature. Well-known geobotanical methods were used to study epigenic lichen groups and to account for their abundance and biomass. The occurrence of epigenic, epilithic, and epiphytic lichens in different plant associations was studied. The distribution of epigenic lichen groupings was studied in different plant communities of the Taman Peninsula, depending on soil conditions. Epigee lichens and their groupings can be used as indicators of soil conditions. The distribution of epigeic lichen groups is significantly influenced by the anthropogenic factor .